Aristotle's Rhetoric : Philosophical Essays - Nehamas, Alexander, 1946-; Furley, David J. (Book collections on Project MUSE., 1994)
In the field of philosophy, Plato's view of rhetoric as a potentially treacherous craft has long overshadowed Aristotle's view, which focuses on rhetoric as an independent discipline that relates in complex ways to dialectic and logic and to ethics and moral psychology. This volume, composed of essays by internationally renowned philosophers and classicists, provides the first extensive examination of Aristotle's Rhetoric and its subject matter in many years. One aim is to locate both Aristotle's treatise and its subject within the more general context of his philosophical treatment of other disciplines, including moral and political theory as well as poetics. The contributors also seek to illuminate the structure of Aristotle's own conception of rhetoric as presented in his treatise.The first section of the book, which deals with the arguments of rhetoric, contains essays by M. F. Burnyeat and Jacques Brunschwig. A section treating the status of the art of rhetoric features pieces by Eckart Schütrumpf, Jürgen Sprute, M. M. McCabe, and Glenn W. Most. Essays by John M. Cooper, Stephen Halliwell, and Jean-Louis Labarriere address topics related to rhetoric, ethics, and politics. The final section, on rhetoric and literary art, comprises essays by Alexander Nehamas and Andre Laks.Originally published in 1994.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.